Analysis of Business Development at Banana Chips MSMEs with Red Ocean Strategy - Nurhaliza, Arridha Lutfia; Rr. Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The banana chip industry in Lampung Province is growing rapidly due to the high production of bananas in the area. Banana is one of the leading commodities along with coffee and pepper. Although bananas are usually sold in their raw form, due to their perishability, the banana chip industry has become a more durable alternative. This study aims to provide light on Askha Jaya's business development practices, specifically whether or not the company continues to use the Red Ocean Strategy approach to rivalry in the market. Interviews and written records serve as main and secondary sources of information. The tools used for data analysis include SWOT, IFE, and matrices, as well as a scheme. Matrixes for internal and external factors, as well as four-step framework and strategy canvas. And currently, Askha Jaya Banana Chips still use Samudera Merah, according to research findings.